2019
DOI: 10.1002/jcb.28344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the CSF1R inhibitor PLX3397 on remyelination of corpus callosum in a cuprizone‐induced demyelination mouse model

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease affecting the central nervous system (CNS). Despite introducing multiple immunomodulatory approaches for MS, there are still major concerns about possible ways for improving remyelination in this disease. Microglia exert essential roles in regulation of myelination processes, and interaction between colony-stimulating factor 1 (CSF1) with its receptor CSF1R is considered as a key regulator of microglial differentiation and survival. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 54 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…Many studies have interrogated the role of microglial cells in inflammatory diseases of the CNS using a depleting dose of a CSF1R inhibitor. In particular, studies have utilized both the C57BL/6 EAE and cuprizone models to understand the role of microglia and infiltrating macrophages in MS 22,29,50 . Some studies have shown marked improvement in EAE disease score in the presence of a CSF1R inhibitor 29 as well as a blockade of demyelination in the cuprizone model 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have interrogated the role of microglial cells in inflammatory diseases of the CNS using a depleting dose of a CSF1R inhibitor. In particular, studies have utilized both the C57BL/6 EAE and cuprizone models to understand the role of microglia and infiltrating macrophages in MS 22,29,50 . Some studies have shown marked improvement in EAE disease score in the presence of a CSF1R inhibitor 29 as well as a blockade of demyelination in the cuprizone model 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of microglial activation with minocycline in mice undergoing cuprizone treatment reduced demyelination, highlighting the detrimental function of microglia in this model (Skripuletz et al, 2010). Along this line, depletion of microglia by the administration of the CSF1R inhibitor PLX3397 during the remyelination phase resulted in increased remyelination rate and improved recovery of motor deficits (Tahmasebi et al, 2019). Short term treatment with the CSF1R kinase inhibitor BLZ945 also led to reduced microglia numbers which correlated with less demyelination and higher oligodendrocyte numbers in the corpus callosum.…”
Section: Detrimental Microglial Responses In Cuprizone-induced Demyelmentioning
confidence: 79%
“…In this context, the study using aging mice showed that repopulation of microglia after elimination by the CSF1R inhibitor restores microglial morphology (repopulated cells resemble young cells) and ameliorates age-related cognitive dysfunction [25]. Other studies indicate that the depletion of microglia also improves neurological deficits in mouse models of demyelination-related diseases, such as catatonia [26] and multiple sclerosis [27,28].…”
Section: Discussionmentioning
confidence: 99%